IMPLEMENTATION OF ZAKAT REDUCTION POLICY FOR STATE CIVIL SERVANTS BASED ON THE REGULATION OF THE MAYOR OF LHOKSEUMAWE NUMBER 33 OF 2017 CONCERNING THE MAMAGEMENT MECHANISM OF ZAKAT, INFAQ, SHADAQAH AND WAQAF - Amru Alba; Fidhia Aruni; Rudi Kurniawan; Muhammad Muhammad (Dinamika : Jurnal Ilmiah Ilmu Administrasi Negara, 2021)
The implementation of the Zakat Reduction Policy for State Civil Servants (ASN) based on the Regulation of the Mayor of Lhokseumawe Number 33 of 2017 concerning the Zakat Management Mechanism "by taking the research location at the Baitul Mal Office of Lhokseumawe City. The purpose of this study is to describe and analyze the implementation of the Zakat Reduction Policy for State Civil Servants (ASN) based on the Regulation of the Mayor of Lhokseumawe Number 33 of 2017 concerning the Mechanism of Zakat Management.